Discretionary intake among Australian adults: prevalence of intake, top food groups, time of consumption and its association with sociodemographic, lifestyle and adiposity measures. Issue 9 (25th January 2019) - Fayet-Moore, Flavia; McConnell, Andrew; Cassettari, Tim; Tuck, Kate; Petocz, Peter; Kim, Jean
Abstract: Objective: To profile discretionary food and beverage (DF) consumption among Australian adults. Design: Cross-sectional analysis. Dietary and sociodemographic data were used to profile DF intake. Prevalence of DF consumption, DF servings (1 serving=600 kJ), nutrient contribution from DF and top DF food groups by self-reported eating occasions were determined. DF consumers (>0 g) were classified according to quartile of DF intake and general linear models adjusted for age and sex were used to determine associations. Setting: 2011–12 National Nutrition and Physical Activity Survey (NNPAS). Participants: Adults aged ≥19 years ( n 9341) who participated in the NNPAS 2011–12. Results: Most adults consumed DF (98 %) and over 60 % exceeded 3 DF servings/d, with a mean of 5·0 (se 0·0) DF servings/d. Cakes, muffins, scones, cake-type desserts contributed the most DF energy (8·4 %) of all food groups, followed by wines (8·1 %), pastries (8·0 %) and beers (6·1 %), with all these food groups consumed in large portions (2·3–3·0 DF servings). Lunch and dinner together contributed 45 % of total DF energy intake. High DF consumers had an average of 10 DF servings, and this group contained more younger adults, males, low socio-economic status, lower usual fruit intake and higher mean waist circumference, but not higher BMI. Conclusions: A focus on DF consumed in large portions at lunch and dinner may help improve interventions aimed at reducing DF intake and addressing negative adiposity-related measures found in high DF consumers.